Short Communication: Morphological and molecular description of Contracaecum sp. larvae (Nematoda: Anisakidae) in common rudd fish of the Shurkul Reservoir of Uzbekistan - BAKHROM B. SOATOV; ABDURAKHIM E. KUCHBOEV; ROKHATOY R. KARIMOVA; OYBEK O. AMIROV (Society for Indonesian Biodiversity, 2023)
Abstract. Soatov BB, Kuchboev AE, Karimova RR, Amirov OO. 2023. Short Communication: Morphological and molecular description of Contracaecum sp. larvae (Nematoda: Anisakidae) in common rudd fish of the Shurkul reservoir of Uzbekistan. Biodiversitas 24: 2031-2036. The common rudd (Scardinius erythrophthalmus Linnaeus 1758) is freshwater fish widely spread in Uzbekistan, including reservoirs of the Bukhara Province, Uzbekistan. The study aimed to perform the morphological and molecular identification of the larvae of nematode Contracaecum sp. found in common rudd fish in the Shurkul Reservoir of the Bukhara Province. These larvae were similar to species of the genus Contracaecum based on their morphological characteristics. The molecular data, according to the results of the phylogenetic tree based on nucleotide sequences of the 18S gene of rDNA, the samples of larvae showed a close relationship with haplotype Contracaecum rudolphii Hartwich, 1964 E. Therefore, to increase the reliability of this information, nucleotide sequences of the gene 28S of rDNA were verified. As a result of this study, these larvae were very close to the haplotype of C. rudolphii B (AF 226579). Also, the common rudd fish was registered as an intermediate host for the larvae of this nematode. The prevalence of this fish with larvae of C. rudolphii B was 10.5%, and the intensity of infection was 1-18 copies. Thus, the larvae of the species C. rudolphii B are registered for the first time in Uzbekistan, and the common rudd fish was noted as an intermediate host.